Efficacy of afatinib for pulmonary adenocarcinoma with leptomeningeal metastases harboring an epidermal growth factor receptor complex mutation (exon 19del+K754E): A case report. Issue 43 (23rd October 2020) - Ma, Chunhua; Liu, Mei; Mu, Ning; Li, Jinduo; Li, Lin; Jiang, Rong
Abstract: Rationale: Liquid biopsy of cerebrospinal fluid (CSF) and sequencing of cell-free DNA has rarely been used to identify epidermal growth factor receptor (EGFR) mutations, which can guide the design of precise, personalized treatment for patients with leptomeningeal metastasis from lung adenocarcinoma. Patient concerns: A 42-year-old woman with lung adenocarcinoma and leptomeningeal metastasis was admitted to our hospital on March 31, 2019. She exhibited no response to treatment with gefitinib, osimertinib, or chemoradiotherapy and was in critical condition, with an expected survival of <4 weeks. Diagnosis: Next-generation sequencing of CSF and peripheral blood samples identified an EGFR complex mutation (exon19del+K754E). Interventions: On April 10, 2019, the patient started oral afatinib (40 mg po qd), but she developed a grade III oral mucosal reaction 1 week later. The afatinib dose was reduced to 30 mg po qd. Outcomes: At the follow-up examination on May 15, 2019, the patient reported relief from headaches. Enhanced magnetic resonance imaging revealed a reduction in abnormal leptomeningeal enhancement, and the CSF pressure and carcinoembryonic antigen levels were also reduced. The patient continued to respond to afatinib treatment (30 mg once daily) with minimal adverse effects. Lessons: This is the first case report of clinical improvement after afatinib treatment in a patient with lung adenocarcinoma and leptomeningeal metastasis harboring an EGFR complex mutation (exon19del+K754E), and thus provides a clinical reference for treatment with afatinib of cancers harboring EGFR compound mutations.